Selenium Regulates Hypothalamic Control of Energy Metabolism in a Sexually Dimorphic Manner. (29th May 2020) - Torres, Daniel; Pitts, Matthew; Seale, Lucia; Hashimoto, Ann; An, Katlyn; Hui, Katherine; Berry, Marla
Abstract: Objectives: The trace element selenium (Se) is known mainly for its antioxidant properties and is critical for proper brain function. The role of Se in regulating energy metabolism, and the sexually dimorphic nature of Se functions, however, are underappreciated, and warrant increased attention. Recent work in our lab has highlighted the importance of Se utilization in hypothalamic regulation of energy metabolism. Dietary Se is incorporated into selenoproteins in the form of the unique amino acid selenocysteine (Sec). The objective of this study was to assess the role of selenoproteins in Agouti-related peptide (Agrp)-positive neurons, an orexigenic sub-population of the hypothalamus. Methods: We generated mice with Agrp-Cre-driven deletion of selenocysteine tRNA (Trsp-Agrp KO mice), which is essential for Sec incorporation into selenoproteins, thus ablating selenoprotein synthesis in Agrp-positive neurons. The metabolic phenotype of Trsp-Agrp KO mice challenged with a high-fat diet was characterized via glucose tolerance test (i.p. injection) and the use of analytical chambers to measure food intake and respiratory metabolism. Prior to sacrifice, mice were challenged with leptin (i.p. injection) to assess neuronal leptin responsivity via immunohistochemistry and western blot. Brown adipose tissue (BAT) morphology and thermogenic protein expression were also analyzed. Results: Female Trsp-Agrp KO mice displayed resistance to diet-induced obesity, which was accompanied by improved glucose tolerance and elevated energy expenditure levels without changes in food intake. Female Trsp-Agrp KO mice also had greater leptin sensitivity and showed signs of elevated BAT thermogenesis. Male Trsp-Agrp KO mice displayed no changes in metabolic phenotype. Conclusions: Loss of selenoproteins in Agrp-positive neurons of the hypothalamus promotes energy expenditure and reduces diet-induced obesity in a sexually dimorphic manner, leading to resistance to a high-fat diet in females. Funding Sources: This work was funded by grant support from the National Institute of Diabetes and Digestive and Kidney Diseases (MJB) and Ola HAWAII, a grant from the National Institute on Minority Health and Health Disparities.